1998
DOI: 10.1063/1.368896
|View full text |Cite
|
Sign up to set email alerts
|

Transient enhanced diffusion and defect microstructure in high dose, low energy As+ implanted Si

Abstract: (001) CZ silicon wafers were implanted with As+ at 100 keV to a dose of 1×1015/cm2 in order to produce a continuous amorphous layer to a depth of about 120 nm. Furthermore, the implant condition was such that the peak arsenic concentration was below the arsenic clustering threshold. Subsequently, a second As+ or Ge+ implant was performed at 30 keV to doses of 2×1015/cm2, 5×1015/cm2 and 1×1016/cm2, respectively, into the as-implanted samples. All of the samples were annealed at 800 °C for 1 h. The second implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Krishnamoorthy et al 10 have reported increased arsenic diffusion in silicon due to damage beyond the end of range defects created by an arsenic implant, which might explain the increased arsenic diffusion seen in our ion beam synthesized Si 1Ϫx Ge x layers. Furthermore, Jones et al 11 reported that low-temperature amorphizing implants led to dislocation loops which did not hamper the flow of interstitials across the amorphous/crystalline interface.…”
Section: Discussionmentioning
confidence: 65%
“…Krishnamoorthy et al 10 have reported increased arsenic diffusion in silicon due to damage beyond the end of range defects created by an arsenic implant, which might explain the increased arsenic diffusion seen in our ion beam synthesized Si 1Ϫx Ge x layers. Furthermore, Jones et al 11 reported that low-temperature amorphizing implants led to dislocation loops which did not hamper the flow of interstitials across the amorphous/crystalline interface.…”
Section: Discussionmentioning
confidence: 65%
“…For example, As concentrations (peak values of 2 x 10 21 /cm 3 for the lowest dose implant) are substantially above the expected solid solubility limit of 1-3 x 10 20 /cm 3 [5], and As clustering is non-negligible [6]. Reflectance Wavelength, nm Figure 1.…”
Section: Resultsmentioning
confidence: 97%
“…Experiments suggest that a large fraction of electrically inactive As atoms are either in substitutional lattice sites in the form of As clusters, 11 or, for high dopant concentrations, coherent crystalline precipitates. 12,13 The latter are expected to be present both in bulk Si and SIMOX, although the clusters containing vacancies should be favored in SIMOX compared to bulk Si due to the higher vacancy concentration in this type of substrate.…”
Section: Introductionmentioning
confidence: 99%